1996
DOI: 10.1111/j.1600-0447.1996.tb09850.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluoxetine on anxiety and depression symptoms in cancer patients

Abstract: Little has been done to study the effectiveness of antidepressants in controlling anxiety/depression in a population of cancer patients. A double-blind placebo-controlled study was therefore designed to assess the effectiveness of 20 mg fluoxetine. Of 115 cancer patients who fulfilled entry criteria for levels of distress, 45 patients were randomized to a fluoxetine treatment group (FA) and 46 patients to a placebo group (PA) after a 1-week placebo period designed to exclude placebo responders. The Montgomery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 10 publications
0
106
0
1
Order By: Relevance
“…Chronic treatment with antidepressants, including fluoxetine, has been found to be effective in alleviating the depression associated with multiple sclerosis (Schiffer and Wineman 1990), stroke (Lauritzen et al 1994), HIV infection (Rabkin et al 1994), cancer (Razavi et al 1996), and neurodegenerative diseases (Alexopoulos 1996). Because these medical conditions are also associated with dramatic immune activation and cytokine secretion (Dinarello and Wolff 1993;Rothwell et al 1996;Yirmiya et al 1999), it may be suggested that at least part of the effects of fluoxetine (and possibly other antidepressants) in these conditions is in attenuating sickness behavior symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic treatment with antidepressants, including fluoxetine, has been found to be effective in alleviating the depression associated with multiple sclerosis (Schiffer and Wineman 1990), stroke (Lauritzen et al 1994), HIV infection (Rabkin et al 1994), cancer (Razavi et al 1996), and neurodegenerative diseases (Alexopoulos 1996). Because these medical conditions are also associated with dramatic immune activation and cytokine secretion (Dinarello and Wolff 1993;Rothwell et al 1996;Yirmiya et al 1999), it may be suggested that at least part of the effects of fluoxetine (and possibly other antidepressants) in these conditions is in attenuating sickness behavior symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…fluoxetine and paroxetine) 71 as well as tricyclic antidepressants (TCAs; e.g. amitriptyline and desipramine) 74 . In addition, some antidepressants (e.g.…”
Section: Use Of Antidepressants and Cancermentioning
confidence: 99%
“…Between half to 100% of participants were female. Three studies were multicentre trials (Razavi et al, 1996;Fisch et al, 2003;Morrow et al, 2003) and three were single-centre trials (Van Heeringen and Zivkov, 1996;Musselman et al, 2001;Roscoe et al, 2005).…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…The six pharmacological studies were randomised placebocontrolled trials conducted in the United States of America (n ¼ 4) (Musselman et al, 2001;Fisch et al, 2003;Morrow et al, 2003;Roscoe et al, 2005) and Belgium (n ¼ 2) (Razavi et al, 1996; Box 1 Search strategy terms Van Heeringen and Zivkov, 1996). The mean sample size of intervention and control groups was 83 (range 20 -277 patients) and 83 (range 20 -272 patients), respectively.…”
Section: Pharmacological Studiesmentioning
confidence: 99%